Fibroblast Growth Factors: Biology, Function, and Application for Tissue Regeneration. (11th October 2010) - Yun, Ye-Rang; Won, Jong Eun; Jeon, Eunyi; Lee, Sujin; Kang, Wonmo; Jo, Hyejin; Jang, Jun-Hyeog; Shin, Ueon Sang; Kim, Hae-Won
Abstract : Fibroblast growth factors (FGFs) that signal through FGF receptors (FGFRs) regulate a broad spectrum of biological functions, including cellular proliferation, survival, migration, and differentiation. The FGF signal pathways are the RAS/MAP kinase pathway, PI3 kinase/AKT pathway, and PLCγ pathway, among which the RAS/MAP kinase pathway is known to be predominant. Several studies have recently implicated the in vitro biological functions of FGFs for tissue regeneration. However, to obtain optimal outcomes in vivo, it is important to enhance the half-life of FGFs and their biological stability. Future applications of FGFs are expected when the biological functions of FGFs are potentiated through the appropriate use of delivery systems and scaffolds. This review will introduce the biology and cellular functions of FGFs and deal with the biomaterials based delivery systems and their current applications for the regeneration of tissues, including skin, blood vessel, muscle, adipose, tendon/ligament, cartilage, bone, tooth, and nerve tissues.